Igneous Rock Associations 12: A Geologist’s Look at Archaeological Ceramics and Glass - Owen, J.; Greenough, John (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2014)
Ceramics and glass represent synthetic metamorphic rocks and obsidian, respectively. Consequently, it is not surprising that many archaeologists have collaborated with geologists on projects dealing not only with lithic artifacts, but with ceramic and glass objects as well. This paper presents an overview of these latter two materials from a geological perspective, considering in turn how they are characterized and classified, their ages constrained, provenance and in some instances use determined, and how they were made.